Combined Role of Spirulina and Exercise-Based Interventions in Individuals with Overweight and Obesity: A Systematic Review and Meta-Analysis - Yasul, Yavuz; Akbulut, Taner; Cinar, Vedat; Yasul, Muhammet Enes; Migliaccio, Gian Mario; Lee, Do-Youn (Mdpi, 2026)
Background: Spirulina supplementation combined with structured exercise may improve obesity-related metabolic dysfunctions. This research examined whether this combination enhances body composition, glucose levels, lipid profile, and cardiorespiratory fitness in overweight and obese adults. Methods: Following PRISMA 2020 guidelines, a systematic search of Scopus, PubMed, and Web of Science identified randomized controlled trials (RCTs) evaluating spirulina (1-6 g/day) combined with structured exercise in individuals with overweight and obesity (BMI >= 25). The search retrieved 91 records, of which 10 studies met the inclusion criteria and were included in the systematic review. Nine studies provided sufficient post-intervention data and were included in the quantitative meta-analysis using a random-effects model, with heterogeneity assessed using tau 2, Q, and I2 statistics. Publication bias was evaluated using rank correlation, regression-based tests, trim-and-fill, and fail-safe N analyses. Results: Combined spirulina supplementation and structured exercise (6-12 weeks) was associated with reductions in BMI (-1.34 kg/m2), body fat percentage (-3.03%), fasting glucose (-14.47 mg/dL), LDL-C (-12.68 mg/dL), and triglycerides (-9.81 mg/dL), along with increases in VO2max (3.25 mL/kg/min) and HDL-C (4.21 mg/dL). Effect estimates were generally larger in combined exercise-spirulina subgroups, particularly in HIITsupp and R-AEsupp conditions, whereas supplementation-only comparisons demonstrated smaller and less consistent changes. Inflammatory markers and adipokines (CRP, TNF-alpha, MCP-1, IL-6, IL-8) showed favorable directional changes in individual trials. Conclusions: Spirulina combined with structured exercise was associated with changes in anthropometric, glycemic, cardiorespiratory, and lipid parameters in individuals with overweight or obesity.
Keywords: spirulina; exercise; physical activity; overweight; obesity; VO2max; lipid profile